Program planning for the community teaching hospital medical library. - McCorkel, J (1985)
To respond to the increasing demand for information from medical educators and clinicians and to persuade administrators to purchase the newly available microcomputer library systems, medical librarians in community teaching hospitals may find it useful to engage in intermediate term (for example, five-year) program planning. To increase the probability that the plan which emerges will be implemented, the planning process should fit the organizational nexus. Planning involves needs assessment, prioritized program elements, a written plan, and facilities planning (if applicable), which lead to program implementation. Components of a model program plan are presented.